Women's organisations, maternal knowledge, and social capital to reduce prevalence of stunted children: evidence from rural Nepal - Imai, K; Eklund, P; Felloni, F (University of Oxford, 2003)
This study analyses behaviour of women community based organisations in two districts in Nepal in reducing prevalence of child malnutrition in member households. Our survey focused on three sets of women organisations: those that receive intensive external support are compared with those that receive only moderate assistance, and those that are entirely autonomous, so-called Mothers' Groups. Higher capabilities of the Mothers' Group are found associated with lower underweight. The study also demonstrates that enhanced knowledge diffusion, combined with growth promotion, represents an effective instrument for empowering rural women in acting to reduce prevalence of chronic malnutrition.